Social-Economic and Children’s Nutritional Status in Bengkulu Province - Sofais, Danur Azissah Roesliana; Rustandi, Handi; Suyanto, Jipri; Hidayat, Yance (JOSING: Journal of Nursing and Health, 2022)
This study aims to determine the factors related to the nutritional status of children in Bengkulu Province due to COVID-19 that affect economic conditions and make the healthy situation worse than before, especially child nutrition. The method used is a cross-sectional study conducted through an online questionnaire. The results of this study indicate that the factors that are significantly related to the nutritional status of children are; financially inadequate (AOR = 2.32; 95% CI: 1.50 to 3.60, P<0.0001), employed (AOR = 3.03; 95% CI: 193 to 4.76, P< 0.0001), living in urban areas (AOR = 1.59; 95% CI: 1.03 – 2.43, P: 0.034), local ethnicity (AOR = 1.72; 95% CI: 1.11 to 2, 68, P: 0.016) and low-income family support (AOR = 2.10; 95% CI: 1.34 to 3.28 < P<0.0001). In conclusion, financial condition, employment status, place, ethnicity, and family are related to the nutritional status of children in Bengkulu Province. Keywords: Financial Condition, Employment, Children's Nutritional Status